A Geant4 tool for edge-illumination X-ray phase-contrast imaging. (1st January 2022) - Brombal, L.; Rigon, L.; Arfelli, F.; Menk, R.H.; Brun, F.
Abstract: The PEPI project is developing a new experimental facility integrating a chromatic photon-counting detector within an edge-illumination (EI) phase-contrast setup. In this context, a novel Geant4-based simulation tool has been introduced with the aim of defining the optimal design of the experimental setup. The code includes a custom X-ray refraction process and allows simulating the whole EI system, comprising a polychromatic and extended source, absorbing masks, substrates, their movement during acquisition, and X-ray detection. In this paper, a realistic spectral detector model is introduced and its energy response validated against experimental data acquired with synchrotron radiation at energies between 26 and 50 keV. Moreover, refraction and transmission images of a plastic phantom are reconstructed from simulation data and successfully compared with theoretical predictions. Finally, an optimization study aiming at finding the effect of the X-ray focal spot size (i.e. spatial coherence) on image quality is presented; the results suggest that, in the considered configuration, the system can tolerate source sizes up to 30 μm, while, for a fixed exposure time, the best signal-to-noise ratio in refraction images is found for source sizes in the order of 10 to 15 μm.